Synthesis of a Naphtho-pyrido-Annulated Iodonium Salt and Pd-Catalyzed Transformation to 7H-Naphtho[1,8-bc][1,5]naphthyridine - Letessier, Julien; Geffe, Mario; Schollmeyer, Dieter; Detert, Heiner (Synthesis, 2013)
Nitropyridylnaphthalene is the central intermediate for the synthesis of naphthonaphthyridine and benzo-δ-carboline. Whereas the Cadogan reaction gives the carboline, transformation of the nitro group to iodo followed by oxidation and cyclization results in an iodonium salt. A twofold Pd-catalyzed amination leads to the naphthyridine.
Keywords: amination; fused-ring systems; heterocycles; iodine; palladium; catalysis